Relationship of Preoperative Hearing loss with Peroperative Ossicular Discontinuity in Chronic Otitis Media (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Chronic Otitis Media (COM) is a common disease in our country. COM with or without cholesteatoma may lead to ossicular discontinuity. However, the discontinuity of the ossicular chain is usually confirmed during operation. The purpose of the study was to find out the correlation between preoperative hearing loss and the status of ossicular chain at surgery.Methods: This cross-sectional study was conducted in the department of otolaryngology- Head & neck surgery, Bangabandhu Sheikh Mujib Medical University from January 2013 to June 2014. At least 113 patients of COM were selected as per inclusion and exclusion criteria. Relevant data were collected in a predesigned data collection sheet and analyzed with standard statistical method. Statistically significant inferred for P value